Optimization of a Monopolar Electrode Configuration for Hybrid Electrochemical Treatment of Real Washing Machine Wastewater - Aguirre-Quintana, M; Aguirre-Quintana, M; Romero-Figueroa, J; Quijada-Maldonado, E; Abejon-Elias, R (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
This study focuses on the design and optimization of a monopolar electrode configuration for the hybrid electrochemical treatment of real washing machine wastewater. A combined electrocoagulation (EC) and electro-oxidation (EO) system was optimized to maximize pollutant removal efficiency while minimizing energy consumption. The monopolar setup employed mixed metal oxide (MMO) and aluminum anodes, along with a stainless steel cathode, operating under controlled conditions with sodium chloride as the supporting electrolyte. An applied current density of 15 mA cm−2 achieved 90% chemical oxygen demand (COD) removal, 98% surfactant degradation, complete turbidity reduction within 120 min, and pH stabilization near 8. Additionally, electrochemical disinfection achieved <2 MPN/100 mL, with no detectable phenols and the presence of organic anions such as oxalate and acetate. These results demonstrate the effectiveness of an optimized monopolar EC–EO system as a cost-efficient and sustainable strategy for wastewater treatment and potential water reuse. Further studies should focus on refining energy consumption and monitoring reaction by-products to enhance large-scale applicability. © 2025 by the authors.